2022
DOI: 10.3390/jof9010050
|View full text |Cite
|
Sign up to set email alerts
|

MoNap1, a Nucleosome Assemble Protein 1, Regulates Growth, Development, and Pathogenicity in Magnaporthe oryzae

Abstract: Nap1 is an evolutionarily conserved protein from yeast to human and is involved in diverse physiological processes, such as nucleosome assembly, histone shuttling between the nucleus and cytoplasm, transcriptional regulation, and the cell cycle regulation. In this paper, we identified nucleosome assemble protein MoNap1 in Magnaporthe oryzae and investigated its function in pathogenicity. Deletion of MoNAP1 resulted in reduced growth and conidiation, decreased appressorium formation rate, and impaired virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Through RNA sequencing (RNA‐seq) analysis, we previously found that the gene MGG_03970 was upregulated in the Δ Monap1 mutant (Zhang, Chen, et al., 2022 ; Zhang, Wang, et al., 2022 ). To verify the reliability of transcriptome data, we assessed the transcription levels of MGG_03970 in Guy11 and Δ Monap1 mutant using reverse transcription‐quantitative PCR (RT‐qPCR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through RNA sequencing (RNA‐seq) analysis, we previously found that the gene MGG_03970 was upregulated in the Δ Monap1 mutant (Zhang, Chen, et al., 2022 ; Zhang, Wang, et al., 2022 ). To verify the reliability of transcriptome data, we assessed the transcription levels of MGG_03970 in Guy11 and Δ Monap1 mutant using reverse transcription‐quantitative PCR (RT‐qPCR).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a nucleosome assembly protein, MoNap1, that regulates appressorium formation, response to cell wall stresses, cytoplasmic division, and virulence (Zhang, Wang, et al., 2022 ). Based on transcriptome data previously, we screened for differentially expressed genes (DEGs) between the wild‐type Guy11 and Δ Monap1 mutant and identified MGG_03970 .…”
Section: Introductionmentioning
confidence: 99%